Development of a System for Converting Recyclable Materials into Virtual Points - Cosio, Paulo; Brucal, Stanley Glenn E.; De Jesus, Luigi Carlo M.; Peruda Jr., Sergio R.; Samaniego Jr., Leonardo A.; Villarroel, Juan Miguel H.; Yong, Einstein D.; Biron, John Renzy D.; Nevalasca III, Dominador S.; Reyes, Genesis T.; Zamuco, Jeremy Kyle B. (International Journal of Computing Sciences Research, 2023)
Purpose – The study aimed to develop a system that can turn recyclable materials such as PET bottles, papers, and metal containers into virtual point rewards in the form of RAMCoins that can be spent on. Method – The system makes use of an object detection module with a modified dataset that includes PET bottles, paper, and soda cans as trash. This categorized into portions: trash detection, trash weighing, and transaction. The proponents conducted a survey to Asia Pacific College students and after the testing of the project, it had minor malfunctions that led to common problems that can be found in the system. Results – The proponents aim to integrate a reward system for every trash thrown using Arduino tools and android as its supporting wallet. To achieve the functionalities of the project, these should be met: Accuracy for valuing RamCoins, Accuracy for comparing RamCoins to original price of trash, Efficiency of RamCoin generation, and lastly, the Usefulness of the GUI. The result from Accuracy (valuing RamCoins) and Accuracy (comparison on real price) indicated poor ratings. The Efficiency resulted to fair rating. Lastly, the Usefulness marked good rating. Conclusion – The design functions implemented for the software, hardware and mobile application were able to perform accordingly in testing and collect satisfactory results. Upon testing, the system was able to consistently detect right trash and generate RamCoins. Recommendations – Throughout the project testing of the system, the proponents recommend the future researchers to integrate the RamWallet feature, the Earn and Receive system, as one for further simplification of the system. The camera detection through phone can be utilized so it will be more convenient for the users. Practical Implication – The proposed project can help better address the waste disposal problem of every community since it will incentivize people participating the recycling of their trash.